Occurrence of Cyperus root borer, Athesapeuta cyperi Marshall (Curculionidae: Coleoptera: Baridinae) as a minor pest of banana - Padmanaban, B.; Alagesan, A.; Kalita, D.N.; Mustaffa, M.M. (ENTOMON, 2016)
During the course of field investigation in North-eastern region, Guwahati, Assam the banana plants were found infested with the weevil Athesapeuta cyperi and it was a new report.